Photosynthetic response of Chlamydomonas reinhardtii and Chlamydomonas sp. 1710 to zinc toxicity - Zhan, Di; Liu, Yue; Yu, Na; Hao, Chunbo (Frontiers in Microbiology, 2024)
Zinc (Zn) is an essential trace element but can lead to water contamination and ecological deterioration when present in excessive amounts. Therefore, investigating the photosynthetic response of microalgae to Zn stress is of great significance. In this study, we assessed the photosynthetic responses of neutrophilic Chlamydomonas reinhardtii and acidophilic Chlamydomonas sp. 1710 to Zn exposure for 96 hours. The specific growth rate (μ), chlorophyll-a (Chl-a) content, and chlorophyll fluorescence parameters were determined. The results demonstrated that Chlamydomonas sp. 1710 was much more tolerant to Zn than C. reinhardtii, with the half-maximal inhibitory concentration (IC50) values of 225.4 mg/L and 23.4 mg/L, respectively. The μ and Chl-a content of C. reinhardtii decreased in the presence of 15 mg/L Zn, whereas those of Chlamydomonas sp. 1710 were unaffected by as high as 100 mg/L Zn. Chlorophyll fluorescence parameters indicated that the regulation of energy dissipation, including non-photochemical quenching, played a crucial role in Zn stress resistance for both Chlamydomonas strains. However, in the case of C. reinhardtii, non-photochemical quenching was inhibited by 5 mg/L Zn in the first 48 hours, whereas for Chlamydomonas sp. 1710, it remained unaffected under 100 mg/L Zn. Chlamydomonas sp. 1710 also exhibited a 20 times stronger capacity for regulating the electron transfer rate than C. reinhardtii under Zn stress. The light energy utilization efficiency (α) of Chlamydomonas sp. 1710 had the most highly non-linear correlation with μ, indicating the energy utilization and regulation process of Chlamydomonas sp. 1710 was well protected under Zn stress. Collectively, our findings demonstrate that the photosystem of Chlamydomonas sp. 1710 is much more resilient and tolerant than that of C. reinhardtii under Zn stress.